Differentiation of Aspergillus flavus from Aspergillus oryzae Targeting the cyp51A Gene - Sanaz Nargesi; Mahdi Abastabar; Reza Valadan; Sabah Mayahi; Jung-Ho Youn; Mohammad Taghi Hedayati; Seyedmojtaba Seyedmousavi (Pathogens, 2021)
Aspergillus flavus is one of the most important agents of invasive and non-invasive aspergillosis, especially in tropical and subtropical regions of the world, including Iran. Aspergillus oryzae is closely related to A. flavus, and it is known for its economic importance in traditional fermentation industries. Reports of infection due to A. oryzae are scarce. Several studies reported that differentiating these two species in clinical laboratories is not possible using MALDI-TOF or by targeting fungal barcode genes, such as Internal Transcribed Spacer (ITS) and β-tubulin (benA). The species-level identification of causative agents and the determination of antifungal susceptibility patterns can play significant roles in the outcome of aspergillosis. Here, we aimed to investigate the discriminatory potential of cyp51A PCR-sequencing versus that of the ITS, benA and calmodulin (CaM) genes for the differentiation of A. flavus from A. oryzae. In a prospective study investigating the molecular epidemiology of A. flavus in Iran between 2008 and 2018, out of 200 clinical isolates of A. flavus, 10 isolates showed >99% similarity to both A. flavus and A. oryzae. Overall, the ITS, β-tubulin and CaM genes did not fulfil the criteria for differentiating these 10 isolates. However, the cyp51A gene showed promising results, which warrants further studies using a larger set of isolates from more diverse epidemiological regions of the world.